Islam Wasathiyah dalam Perspektif Tafsir Izwaji - Musthofa Musthofa (LP2M Sekolah Tinggi Agama Islam (STAI) Madiun, 2021)
Wasathiyah Islam is a moderate teaching, taking sides with the truth of Islamic teachings between liberal and conservative schools. Wasathiyah Islam has the character of respecting conservative (closed) and liberal (open) ideologies by accommodating liberal Islam, the understanding of free Islam and conservative Islam, which has the character of understanding and operating in a closed way. the Prophet, and the atsar of the companions of the Prophet. Wasathiyah Islam in aqidah includes embracing religion, belief in God, and belief in the Prophet. Wasathiyah Islam in worship includes mahdah worship and gairu mahdah worship.